Estudos de mobilidade de contaminantes no solo e de confiabilidade para avaliar o uso de águas residuárias tratadas em indústrias siderúrgicas - Carvalho, Clara Bandeira de (2021)
In a scenario of increasingly frequent water crises, the reuse of treated wastewater appears as an important water management tool. In this sense, as a way of regulating this activity in the State of Ceará, the state superintendence of the environment (SEMACE) published the COEMA Resolution No. 2, of February 2, 2017, which establishes specific guidelines, criteria, and parameters for non-potable reuse in accordance with regulated modalities. Among the requirements regarding the conditions for reuse application that may involve the discharge of effluent into the soil, the legislation presents the need for a study to model the dispersion of contaminants in the soil. However, there is no specification of the methodology that should be adopted for this type of study. Therefore, it is necessary to group techniques that can help in modeling the contaminants’ dispersion. The present dissertation had the general objective of evaluating the reuse of treated wastewater from sanitary and industrial wastewater treatment plants in a steel industry by studying the mobility of contaminants in the soil and reliability studies of the wastewater treatment systems. For this purpose, leaching column tests were performed using soil samples collected in areas within the industry where the treated wastewater would be reused. Based on the tests, elution curves (breakthrough curves, BTC) were generated to analyze the mobility of contaminants in the soil and obtained the transport parameters (dispersion coefficient, delay coefficient, and dispersivity). The wastewater produced in the steelworks has low concentrations of heavy metals after the treatment systems, with only iron and zinc being contaminants of environmental hazard for wastewater disposal.The low percentage of colloids (clay and organic matter) in the analyzed soils showed the inefficiency of retention of released solutes, facilitating their leaching and subsequent increase in the risks of groundwater contamination. Despite the good reliability of wastewater treatment processes, the non-potable reuse of treated wastewater is possible in the steel industry, but it must be associated with soil management and conservation techniques that increase the capacity of the soil to adsorb the contaminants present, or impermeabilization in the area of plate cooling.